Efficient antibacterial/biofilm, anti-cancer and photocatalytic potential of titanium dioxide nanocatalysts green synthesised using Gloriosa superba rhizome extract. Issue 1 (15th December 2021) - Mahendran, D.; Kavi Kishor, P. B.; Geetha, N.; Manish, T.; Sahi, S. V.; Venkatachalam, P.
Abstract: The biomolecule-coated nanotitania catalysts were synthesised using rhizome extract of Gloriosa superba and the characteristics of the synthesised nanocatalysts were investigated by using various physiochemical methodologies. The antibacterial activity of the biomolecule coated nanotitania catalysts was tested against harmful microbial human pathogens. Nanotitania catalysts were found to be the most potential agent against gram negative bacterium i.e. Staphylococcus epidermidis . An efficient anti-biofilm activity was also observed against biofilm developing bacteria namely S. epidermidis and Pseudomonas aeruginosa . The 50% inhibitory concentration (IC50 ) of nanotitania catalysts noticed was 46.64 and 61.81 µg/mL for MCF-7 (cancer) L929 (normal) cell lines, respectively. Bioengineered nanotitania catalysts exhibited potential anticancer activity against breast cancer cell line. AO/EtBr staining results show distinct morphological variations such as orange and red coloured apoptotic bodies were identified in cancer cells that were treated with nanotitania catalysts. Further, the nuclear changes, mitochondrial depolarization and increased reactive oxygen species (ROS) level were also detected in nanotitania catalysts treated MCF-7 cells by Hoechst, rhodamine and DCFH-DA probe staining techniques. COMET assay confirmed the DNA destruction in the nanotitania treated cancer cells. In addition, the nanotitania catalysts exhibited potential photocatalytic activity against inorganic toxic dyes and the maximum rate of dye degradation was observed for crystal violet. The present results strongly suggest that the biomolecule coated nanotitania catalysts could be used as potential and novel compound towards biomedical as well as photocatalytic applications. Graphical Abstract: UF0001